High rates of resumption of injecting drug use following release from prison among men who injected drugs before imprisonment. (21st June 2022) - Curtis, Michael; Winter, Rebecca J.; Dietze, Paul; Wilkinson, Anna L.; Cossar, Reece D.; Stewart, Ashleigh C.; Agius, Paul A.; Butler, Tony; Aitken, Campbell; Kirwan, Amy; Walker, Shelley; Stoové, Mark
Abstract: Aims: To estimate incidence of post‐release injecting drug use (IDU) among men who injected drugs before imprisonment and determine factors associated with post‐release IDU frequency. Design, setting, participants: Prospective cohort study of men reporting monthly IDU before a period of sentenced imprisonment in Victoria, Australia, recruited between September 2014 and May 2016 ( n  = 195). Measurements: Any post‐release IDU and IDU frequency was measured via self‐report at 3‐month follow‐up interview. IDU frequency, measured over the preceding month, was categorised as no IDU, irregular IDU (1–4 days IDU) and regular IDU (≥5 days IDU). Incidence of any IDU was calculated at 3 months post‐release. Factors associated with IDU frequency were estimated using ordinal logistic regression. Findings: Most (83%) participants reported post‐release IDU (265 per 100 person‐years, 95% CI, 227–309); with half (48%) reporting regular IDU, 23% irregular IDU and 29% no IDU in the month preceding follow‐up. Poorer psychological well‐being at follow‐up (General Health Questionnaire [GHQ‐12] score; adjusted odds ratio [AOR], 1.18; 95% CI, 1.07–1.29) and post‐release unemployment (AOR, 4.57; 95% CI, 1.67–12.49) were associated with increased IDU frequency. Retention in opioid agonist treatment (AOR, 0.49; 95% CI, 0.24–0.98) was associated with reduced IDU frequency. Non‐linear (inverted‐u) associations between IDU frequency and age (age: AOR, 1.51; 95% CI, 1.17–1.96; age‐squared: AOR, 0.99; 95% CI, 0.99–0.99) and pre‐imprisonment IDU frequency (pre‐imprisonment IDU frequency: AOR, 1.36; 95% CI, 1.15–1.61; pre‐imprisonment IDU frequency‐squared: AOR, 0.99; 95% CI, 0.99–0.99) were found, with odds peaking at age 39 and 19 days IDU, respectively. Longer baseline sentence length was associated with reduced odds of irregular and regular IDU (AOR, 0.99; 95% CI, 0.99–0.99). Conclusion: Among Australian men who inject drugs before imprisonment, resumption of injecting drug use after release from prison appears to be common, with imprisonment seeming to have little impact on reducing injecting drug use behaviour.